PENDAMPINGAN PELATIHAN SISTEM INFORMASI AKUNTANSI PADA UD SLAMET LANGGENG DAN JENANG SUHARSO KECAMATAN SUMBANG KABUPATEN BANYUMAS - Adi Wiratno; Eko S; Warsidi *; Agus Sunarmo (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2022)
This community service activity was carried out at UD Slamet Langgeng, Kebanggan, Sumbang and Jenang Suharso, Ciberem, Sumbang, which were carried out simultaneously to synergize 2 small businesses that were interconnected. UD Slamet Langgeng is engaged in retail business, while Jenang Suharso is a manufacturing business that buys raw materials in the form of flour, sugar, and so on to UD Slamet Langgeng. The PKM team provides assistance to these two types of small and medium enterprises in terms of financial reporting practices that are in accordance with applicable accounting standards. This activity started from April to October 2014 through the scheme of Iptek Bagi Masyarakat (IbM) funded by DIKTI. With this assistance, both partners understand how to make financial reports in accordance with Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP). With financial reporting that is in accordance with applicable accounting standards, in addition to partner management being more professional, it also makes it easier for partners to get access to funding from the bank.